COMPLEMENTARY THERAPIES AND THE LEGACY OF PROPHET JOB IN INDONESIAN THERAPIES TRADITION - Hidayat, Asep Achmad; Pribadi, Syofiah; Supendi, Usman; Samidah, Ida; Ngoc, Vu Thi; Sumarmi, Sumarmi (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
Complementary therapies have recently become increasingly popular in many countries. Likewise, Indonesian people’s interest in complementary and traditional therapies is starting to increase. This can be seen from the large number of visitors to complementary therapy practices in various places. This study will reveal how complementary therapy ,based on the story of the prophet Job As, as an alternative treatment in the form of hydrotherapy, foot stamping and maggot therapy. This study is a literature review that examines various information related to complementary therapies. The literature review in this study was obtained through a systematic search of computerized database (namely Google Scholar, PubMed, Ebscohost, and Proquet) by entering the keywords, ‘Complementary Therapy, Hydrotherapy, Maggot Therapy, Foot beat therapy, and Treatment in the style of the Prophet Job As’. Based on the result of the literature review, it can be concluded that non-parmacological complementary therapy is an alternative treatment method that is effective and has minimal side effects for various health problems. Hydrotherapy can be used for various age groups with various health complaints, ranging from autism, parkinson’s to mothers who are about to give birth and other health problems. Meanwhile, Foot Stamping (HK) is used for various cardiovascular cases as well as other diseases. Maggot therapy is used as debridement therapy with the aim of removing dead tissue in cases of ulcerated wounds. Keywords: Prophet Job, Hydrotherapy, Stamping Feet, Maggot, Biotherapy